PEMANFAATAN TANDAN KOSONG KELAPA SAWIT (Elaeis) DAN SERBUK KAYU JATI (Tectona Grandis) DALAM PEMBUATAN HURUF TIMBUL KOMPOSIT BERUPA PAPAN PARTIKEL - Anerasari Meidinariasty; Fadarina; Muhammad Hadiid Fadhlillah (KINETIKA, 2021)
Composite letter sign can be made from particle board. This study aims to produce composite letters sign in the form of particle board with the raw materials of Empty Bunch of Oil Palm, Teak Sawdust and Low Density Polyethylene (LDPE) recycled plastics using the hot press method. This study used variations in the concentration of NaOH in the alkalization process. The concentration variations used were 0%, 1%, 2%, 3%, 4% and 5%. The particle board was analyzed based on SNI 03-2105-2006 including moisture content, water absorption, density, thickness expansion, modulus of rapture and modulus of elasticity. The results of the analysis showed that in the test of water absorption, density and thickness expansion did not significantly influence the variation in NaOH concentration. However, in the test of water content, modulus of rapture and modulus of elasticity have an effect, this is indicated by the increasing concentration of NaOH, the more the quality of the particle board increases. The particle board used NaOH 5% concentration variations became the most optimum with water content data of 2.85%, modulus of rapture of 194.65 kgf/cm2 and modulus of elasticity of 7007.90 kgf/cm2